Safety and Potential Test Profile of Inactivated Coryza Vaccine in SPF Chickens - Shilva Givanny Saiful; Mohandas Indradji; Diana Indrasanti; Ernes Andesfha (Journal of Applied Veterinary Science And Technology, 2025)
Background: Infectious coryza, caused by Avibacterium paragallinarum, is an acute and highly contagious respiratory disease in chickens that results in high morbidity, growth retardation, and decreased egg production, leading to economic losses in poultry industries. Vaccination is considered the most effective preventive measure, and inactivated vaccines are widely used due to their safety and ability to stimulate protective immunity. Purpose: This study aimed to evaluate the safety and potency of a commercially produced inactivated coryza vaccine using Specific Pathogen-Free (SPF) chickens at the National Quality Testing and Certification Center for Veterinary Drugs (BPMSPH), Indonesia. Method: A descriptive observational approach was used to assess safety and potency in vaccinated SPF chickens. A total of 40 SPF chickens four weeks old were used and divided into a vaccinated group and a control group. The vaccinated group received the inactivated coryza vaccine according to standard test procedures, while the control group remained unvaccinated. Clinical observations and local reaction assessments were conducted to evaluate safety, and antibody titers against coryza serotype A were measured to determine potency. Results: Observations showed that 100% of both control and vaccinated chickens exhibited no abnormal clinical signs or coryza reactions. In addition, the vaccine potency test showed that 100% of vaccinated chickens had coryza serotype A antibody titers ≥10. Conclusion: This test confirms that the registered inactivated coryza vaccine formulation meets safety test criteria: 100% of control and vaccinated chickens remained clinically normal, and no abnormal local reactions were observed at the inoculation site. Potency testing demonstrated that all vaccinated chickens developed serotype A antibodies, which are expected to provide protection against coryza infection in the field and improve poultry survival.